2017
DOI: 10.1007/s00767-017-0364-1
|View full text |Cite
|
Sign up to set email alerts
|

Safety-relevant hydrogeological properties of the claystone barrier of a Swiss radioactive waste repository: An evaluation using multiple lines of evidence

Abstract: In Switzerland, the Opalinus Clay -a Jurassic (Aalenian) claystone formation -has been proposed as the first-priority host rock for a deep geological repository for both low-and intermediate-level and high-level radioactive wastes. An extensive site and host rock investigation programme has been carried out during the past 30 years in Northern Switzerland, comprising extensive 2D and 3D seismic surveys, a series of deep boreholes within and around potential geological siting regions, experiments in the interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 24 publications
(31 reference statements)
0
12
0
Order By: Relevance
“…It was found that most faults occur in the clay-rich facies types and intervals. This probably reflects the low shear strength of the investigated clay-rich sections which can be attributed to the anisotropy of the mechanical properties (Gautschi 2017), favoring the development of fault planes aligned subparallel to bedding (Orellana et al 2018a;. Brittle fault planes and lithological heterogeneities represent planes of mechanical weakness (Marschall et al 2017), which are prone for reactivation (e.g.…”
Section: Implications Of the Geological-geophysical Investigations And Their Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…It was found that most faults occur in the clay-rich facies types and intervals. This probably reflects the low shear strength of the investigated clay-rich sections which can be attributed to the anisotropy of the mechanical properties (Gautschi 2017), favoring the development of fault planes aligned subparallel to bedding (Orellana et al 2018a;. Brittle fault planes and lithological heterogeneities represent planes of mechanical weakness (Marschall et al 2017), which are prone for reactivation (e.g.…”
Section: Implications Of the Geological-geophysical Investigations And Their Resultsmentioning
confidence: 96%
“…The preferred alignment of phyllosilicates is related to bedding, which causes anisotropic hydraulic and mechanical properties (e.g. Gautschi 2017).…”
Section: Geological Settingmentioning
confidence: 99%
“…Rock fractures can greatly influence the hydrological properties and control the mechanical behaviour of a rock mass. The hydraulic and mechanical properties of rock fractures are of considerable interest in several areas of rock engineering, such as near-field modelling of hydraulic processes around radioactive waste repositories [1,2], underground tunnels [3,4] and storage caverns [5,6], rock slope stability [7,8], petroleum and geothermal reservoirs [9], and solute transport [10]. Single fractures, the elementary unit of a fractured rock mass, have become a research focus.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, existing models assume releases of Se as Se(IV) and Se(VI) oxyanions. However, thermodynamic calculations suggest that Se should be in lower oxidation states (-II and 0) due to interactions with the iron from the canister materials or due to developed reducing conditions within the host rock (e.g., diffusion through clays; Basu et al, 2007;Beauwens et al, 2005;Descostes et al, 2008;Gautschi, 2017). In fact, solid samples containing Se(0) and Se(IV) next to each other originating from reducing environments in Boom Clay have been reported (e.g., Breynaert et al, 2010;Hoving, 2018).…”
Section: Reactivity Within the Host Rock: Mobility And Dispersion Of Se Speciesmentioning
confidence: 99%